2009
DOI: 10.1002/micr.20698
|View full text |Cite
|
Sign up to set email alerts
|

Free flap options for reconstruction of complicated scalp and calvarial defects: Report of a series of cases and literature review

Abstract: With its evident structural and functional advantages, fasciocutaneous flaps were suitable for larger scalp defect only and myocutaneous flaps can be considered as an excellent reconstructive option for complicated scalp and calvarial defects, especially where dead space coexists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
84
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(87 citation statements)
references
References 32 publications
(35 reference statements)
2
84
0
1
Order By: Relevance
“…[5][6][7][8] However, because of the distance between the skull base and the submandibular region, especially when the anterior skull base is accessed via the subcranial approach, vein grafts are often required for the anastamosis of free flaps. 1,9 Hussussian and Reece 10 have reported that the caliber of the STV is insufficient for microvascular anastomosis in scalp reconstruction. In addition, some types of anterolateral thigh free flap 11,12 and radius forearm free flap 13 require the anastomosis of 2 sets of drainage veins, for example, 2 sets of accompanying veins to the vascular pedicle with different back-flow strengths, a comitant vein and a cephalic vein, for secure tissue transfer.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8] However, because of the distance between the skull base and the submandibular region, especially when the anterior skull base is accessed via the subcranial approach, vein grafts are often required for the anastamosis of free flaps. 1,9 Hussussian and Reece 10 have reported that the caliber of the STV is insufficient for microvascular anastomosis in scalp reconstruction. In addition, some types of anterolateral thigh free flap 11,12 and radius forearm free flap 13 require the anastomosis of 2 sets of drainage veins, for example, 2 sets of accompanying veins to the vascular pedicle with different back-flow strengths, a comitant vein and a cephalic vein, for secure tissue transfer.…”
Section: Discussionmentioning
confidence: 99%
“…T he anterolateral thigh (ALT) flap, first described as a septocutaneous perforator-based flap by Song et al (1) in 1984, has recently gained popularity and has become an important option for reconstruction of multiple anatomical locations such as the head and neck (3)(4)(5)(6)(7)9,10,(12)(13)(14)16,(18)(19)(20)(21)(22)(23)(25)(26)(27)(28)(29)(30)32,34,36,38,39,(41)(42)(43), upper (15)(16)(17)(18)(19)26,32,35,37,38,42) and lower (8,(16)(17)(18)(19)22,24,…”
mentioning
confidence: 99%
“…The popularity of the 'work-horse' ALT flap is often attributed to its multiple advantages, which can be divided into three categories: pedicle, flap design and operative technique (1,2,6,7,13,14,21,26,38,(44)(45)(46). With regard to the pedicle, the ALT flap has a long pedicle with good calibre, which can be located and dissected out before committing to the final flap design.…”
mentioning
confidence: 99%
“…Another advantage is the adjustable thickness of the flap to individual needs by removing the deep fascia and subcutaneous fat. 13 The main disadvantages of this procedure are its duration, the risk of flap loss, and the generally nonhair-bearing reconstruction. 13,14 For the cosmetic rehabilitation of the nonhairbearing skin cover, if the patient is very concerned about the hair loss, the flap offers the possibility to transplant hair follicles.…”
Section: Discussionmentioning
confidence: 99%
“…2,[8][9][10] Surgical options to reconstruct large scalp and forehead defects include primary closure, skin grafting, local flaps, tissue expansion, and microsurgical tissue transfer. [11][12][13] The correct option must be chosen according to individual patientspecific parameters.…”
Section: Discussionmentioning
confidence: 99%